2005
DOI: 10.1007/s00417-005-0043-2
|View full text |Cite
|
Sign up to set email alerts
|

Fundus autofluorescence in children and teenagers with hereditary retinal diseases

Abstract: Fundus autofluorescence may visualise disease-specific distributions of lipofuscin in the retinal pigment epithelium, often not (yet) visible on ophthalmoscopy. AF images can be used in children to differentiate hereditary retinal diseases and to facilitate follow-up controls. In many cases, four single images are sufficient to analyse the AF pattern.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 30 publications
5
30
1
5
Order By: Relevance
“…32 In various degenerative retinal disorders, increased FAF correlated with lipofuscin accumulation, whereas reduced or absent FAF indicated blockage (eg, retinal vessels), loss of RPE cells, or absence of RPE phagocytosis. 26,27,[33][34][35][36][37][38][39][40] The patterns of FAF distribution in RP patients observed in this study are similar to those reported previously. Ophthalmoscopically preserved areas of RPE at the posterior pole correspond to detectable FAF.…”
Section: Discussionsupporting
confidence: 86%
“…32 In various degenerative retinal disorders, increased FAF correlated with lipofuscin accumulation, whereas reduced or absent FAF indicated blockage (eg, retinal vessels), loss of RPE cells, or absence of RPE phagocytosis. 26,27,[33][34][35][36][37][38][39][40] The patterns of FAF distribution in RP patients observed in this study are similar to those reported previously. Ophthalmoscopically preserved areas of RPE at the posterior pole correspond to detectable FAF.…”
Section: Discussionsupporting
confidence: 86%
“…Estudos mostram que áreas com aumento de autofluorescência são obtidas através do acúmulo da lipofuscina, e posteriormente, quando há morte das células fotorreceptoras e conseqüente atrofia, essa área mostra diminuição da autofluorescência, sugerindo que o exame de autofluorescência seja um bom marcador para a integridade do epitélio pigmentar da retina, podendo ser útil para investigar a evolução das distrofias da retina (7) . A alteração do ciclo visual nos casos de distrofias de retina causa acúmulo de lipofuscina no EPR e conseqüente morte precoce das células.…”
Section: Discussionunclassified
“…O aumento anormal de A2E predispõe a disfunção e/ou morte do EPR seguido de perda dos fotorreceptores e diminuição da visão (6) . Estudos mostram que há correspondência entre áreas de autofluorescência diminuídas e áreas de perda de células fotorreceptoras, sugerindo que a autofluorescência seja um bom marcador para a integridade do EPR, podendo ser útil para investigar a evolução das distrofias da retina (1,(7)(8) . As distrofias retinianas têm caráter hereditário e causam perda progressiva da função das células fotorreceptoras e diversos sintomas que variam conforme o tipo de lesão.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Sol gözdeki hiper-otofloresan bölge lipofuskin birikimine işaret ederken, lezyonun üst temporalindeki hipo-otofloresan alan ise RPE atrofisine işaret etmekte ve fundus muayenesi ile Evre II olarak saptanan lezyonun aslında Evre III (psödohi-popyon evresinin başlangıcı) olduğunu göster-mekte idi. 4 Bu teknik, lipofuskin birikimi ile karakterize Best hastalığının tanısında ve evrelemesinde de son derece faydalı noninvaziv, hızlı ve kolay bir yöntemdir. 5 FAF incelemede RPE ve altında lipofuskinin birikimi iyi sınırlı ve parlak bir hiper-otofloresan görünüme neden olurken, ilerleyen evrelerde gelişen RPE atrofisi ise keskin sınırlı hipo-otofloresan görünüme yol açmaktadır.…”
unclassified